Unexpected Agreement in Spanish Revisited - Mare, María de Los Angeles (2018)
Verbal agreement in Spanish is materialized as the rightmost morpheme on a verb. When enclitics attach, the expected order is: verbal base + Agr + CL(itic): hága-nAGR-loCL ?Do it!?. Nevertheless, in non-standard Spanish, verbal agreement can appear at the right of the clitic, giving rise to what has been named unexpected agreement: haga-nAGR-loCL-nAGR or haga -loCL-nAGR ?Do it!?. This squib presents and discusses different pieces of data related to unexpected agreement in order to provide some generalizations missed in previous approaches to this topic. The distinction between unexpected morphology and unexpected locus is necessary to revisit the operations involved in this broad phenomenon.